Hubungan Toilet Training, Konstipasi dan Stress dengan Kejadian Enuresis pada Anak Pra-Sekolah Usia 3-6 Tahun: Relationship of Toilet Training, Constipation and Stress with Enuresis Incidence in Pre-School Children Age 3-6 Years - Mimi Amalia Putri (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Enuresis is urinary incontinence where a child should be able to urinate normally but the child can't do it. So, that urine output is not in place or is often called bedwetting. This study aims to determine the relationship between the application of toilet training, constipation and stress with the incidence of enuresis in preschool aged 3-6 years at Tunas Karya Kindergarten, Parakansalak District, Sukabumi Regency 2020. Methods: The research is quantitative non-experimental using a descriptive analytic approach with cross sectional studi design. The sample in this study was 60 guardians of pre-school aged 3-6 years in Tunas Karya Kindergarten, Parakansalak, Sukabumi 2020. Data analysis using Chi-Square Test with SPSS. Results: The results showed that there was a relationship between the application of toilet training and the incidence of enuresis with a P value of 0.000. There is a relationship between constipation and the incidence of enuresis with a P value of 0.001 and there is a relationship between stress and the incidence of enuresis with a P value of 0.000.  Discussion: The 60 respondents who experienced enuresis were 35 (58.3%), while those who did not experienced enuresis were 25 (41.7%). Respondents who did not apply toilet training as many as 34, respondents who experienced constipation as many as 32, respondents who experienced stress as many as 34, there is a relationship between the application of toilet training, constipation and stress with the incidence of enuresis.